Determinan Kepuasan dan Loyalitas Pelanggan: Harga dan Kualitas Produk Wardah - Della Safira; Muhammad Iqbal Fasa (Yayasan Literasi Sains Indonesia, 2024)
This study aims to explore the determinants of customer satisfaction and loyalty towards Wardah products, focusing on the role of price and product quality. In the increasingly competitive cosmetics industry, an in-depth understanding of the factors that influence customer satisfaction and loyalty is crucial to the success of the company. The methodology used in this study is qualitative, with a literature study technique involving the analysis of related literature. The results show that product quality has a significant and positive influence on customer satisfaction. Products that meet customer needs and expectations tend to increase levels of satisfaction, which in turn drives loyalty and repurchase intentions. While price also contributes to the perception of value, product quality remains the main factor determining customer loyalty. This study suggests that Wardah needs to prioritize innovation and product quality improvement in their marketing strategy, accompanied by competitive pricing. In addition, positive customer experiences through good service and effective interactions on social media also need to be considered. These findings provide strategic insights for Wardah management to improve customer satisfaction and loyalty, which are expected to strengthen the company's competitive position in the cosmetics market. Thus, improving quality and wisely managing prices are key to achieving long-term success in this industry.